Secular trend and social gradients in the menarcheal age of girls from eastern Poland between 1986 and 2016 - Saczuk, Jerzy; Wasiluk, Agnieszka; Pytasz, Piotr (Anthropological Review, 2020)
The age at menarche is changing together with the development of society. The intensities of secular trends vary in different countries, regions or even towns and villages. Therefore, the objective of the paper was to assess the changes of the menarcheal age of girls in groups defined by different levels of parental education and the number of children in a family as well as the general index of socioeconomic status. The paper utilises the results of research conducted in the years 1985–1986, 2005–2006 and 2015–2016, covering 11 671 girls aged 10–16 from eastern provinces of Poland. Information about the date of birth, the date of the first period, place of residence, fathers’ and mothers’ education and the number of children in a family was collected. Research material was divided into groups stratified by mother’s education, father’s education, number of children in a family, size of place of residence and the general index of socioeconomic status (SES) was calculated. The results were processed statistically using one-way analysis of variance (ANOVA) and the Newman-Keuls method.In all the assessed groups of girls the acceleration of maturation has been observed. Greater socio-economic differences of the menarcheal age of the respondents were observed in the years 1986–2006, whereas in the years 2006–2016 the differences were smaller. During the assessed period of 30 years, the most intensive acceleration in menarche was observed in the lowest social strata, i.e. in the daughters of parents with primary or vocational education, in those from the largest families and in those who were included in the group with the lowest SES point values. The lowest acceleration in the described indicator of development was found in girls from families with one or two children, whose parents had higher education degrees and the highest SES values.The assessed schoolgirls still demonstrate the existence of social gradients in the menarcheal age but the gradients are smaller than 30 years ago.